Pendidikan Karakter dan Pembangunan Sumber Daya Manusia Keberlanjutan - Sri Suwartini (Universitas Sarjanawiyata Tamansiswa, 2017)
Abstract: Character education is a system of inculcating the character of knowledge, awareness or willingness, and actions to implement those values. Character education is believed to be an important aspect in the improvement of human resources (HR), as it contributes to the development of a community. The character of a qualified society needs to be established and nurtured from an early age, because early age is a